2008
DOI: 10.1158/1055-9965.epi-07-2874
|View full text |Cite
|
Sign up to set email alerts
|

Increased Colorectal Epithelial Cell Proliferation and Crypt Fission Associated with Obesity and Roux-en-Y Gastric Bypass

Abstract: Background and Aims: The relationship between obesity, weight reduction, and future risk of colorectal cancer is not well understood. Therefore, we compared mucosal biomarkers in normal weight individuals [body mass index (BMI), 18.5-24.9 kg/m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 28 publications
11
63
2
Order By: Relevance
“…Findings on insulin resistance and colonic adenomas and cancers are reported by us and others [Sobhani et al 1993[Sobhani et al , 2010Frezza et al 2006]. These results are consistent with those from prospective and interventional studies performed in obese individuals that have shown higher colonic cell proliferation and elevated numbers of ACFs in the colonic mucosa [Calle, 2007;Sainsbury et al 2008].…”
Section: Indirect Bacteria Effects Energy Balance and Metabolismsupporting
confidence: 87%
“…Findings on insulin resistance and colonic adenomas and cancers are reported by us and others [Sobhani et al 1993[Sobhani et al , 2010Frezza et al 2006]. These results are consistent with those from prospective and interventional studies performed in obese individuals that have shown higher colonic cell proliferation and elevated numbers of ACFs in the colonic mucosa [Calle, 2007;Sainsbury et al 2008].…”
Section: Indirect Bacteria Effects Energy Balance and Metabolismsupporting
confidence: 87%
“…That the inverse association for mortality was not limited, in this study, to obesity related cancers but seen for all cancers, argued for bias in such approaches. Furthermore, in a comparative study of mucosal biomarkers in obese patients with BMI >40 kg/m2, Sainsbury et al [18] did not observed any difference on colonic cell proliferation before and 6 months after gastric bypass. In spite of an association between excess body weight and elevated mucosal biomarkers of epithelial cell proliferation and crypt fission as compared to controls, authors concluded that risk for CRC may not be diminished with gastric bypass.…”
Section: No Definitive Evidence Of Weight Reduction and Cancer Prognosismentioning
confidence: 94%
“…Rectal crypt cell mitosis frequency and crypt size were significantly higher in morbidly obese patients compared with normal weight individuals 11. Unexpectedly, mitosis frequency and crypt size were actually increased following weight loss 6 months after RYGB 11.…”
Section: Introductionmentioning
confidence: 93%
“…We have previously measured rectal mucosal epithelial cell mitosis and apoptosis, as well as levels of serum biomarkers of inflammation and mucosal proinflammatory gene expression, in normal weight individuals and morbidly obese (BMI >40 kg/m 2 ) patients before and after Roux-en-Y gastric bypass (RYGB), in order to determine whether differences in crypt epithelial cell turnover were associated with obesity and whether rapid weight loss altered biomarkers of inflammation 11. Rectal crypt cell mitosis frequency and crypt size were significantly higher in morbidly obese patients compared with normal weight individuals 11.…”
Section: Introductionmentioning
confidence: 99%